An Empirical Assessment of Corporate Environmental Crime-Control Strategies - Cohen, Mark A (2013)
Corporate illegality is often attributed to greed by corporate managers and insufficient legal safeguards. Underlying this argument is an explicit critique of corporate crime regulatory systems. Yet there is little systematic investigation of the relative merits of different types or components of crime-control strategies; research comparing more punitive command-and-control strategies with self-regulatory approaches is particularly lacking. In this Article, we assess these crime prevention-and-control mechanisms in the context of individual and situational risk factors that may increase the likelihood of illegal behavior in the environmental arena. We use data drawn from two groups of business managers who participated in a factorial survey (using vignettes) measuring their intentions to participate in two types of environmental offenses. Generally, results show that the most effective regulatory levers are (1) credible legal sanctions and (2) the certainty and severity of informal discovery by significant others in the firm. We conclude by discussing the implications of our findings for regulatory policy and strategy, and for efforts to account for the role of social norms in corporate environmental compliance